Arunachal Pradesh Draft Fifth Five Year Plan 1974-79 Vol. II Planning and Development Department - Planning Commission (Planning Commission, 1973)
To demonstrate and popularise new high yielding varieties, use of fertilizers, plant protection, agricultural implements, double and multicropping to help in increasing crop yields. About 100 such demonstrations were held during the Fourth Plan. 250 demonstrations during the Fifth Plan period the rate of 50 demonstrations per year. The farmers would stand to gain by following improved practices demonstrated in their villages, this make farming more profitable. The proposed Scheme would cover 250 villages and a approximate population of 62,500.
Draft Fifth Five Year Plan 1974-79 Vol. II
Government of Arunachal Pradesh